World After Pandemic: New Socio-Psychological Complex Rises - Easmin Akter Eva (Skad)
Among the rapid and fast growing impact of the Covid-19 pandemic, many hidden realities of our daily lives have become complicated and apparent. Being in this pandemic era, it makes sense that prime focus should be on the sequential process of understanding, adjusting and coping with the running pandemic from a differently compatible perspective. By doing that, the everyday social management of pandemic has rigorously started to show how immensely this public health emergency issue has surfaced, been considered, managed and at times, even caused further marginalisation of sociohistorically disadvantaged groups that struggle hard to find proof in ‘abled’ society already. It is considered that the Covid-19 pandemic as a super transition to a more inclusive society in the newly found spirit of collective action and shared responsibility. Societies are finding alternative ways to reach their goals such as education, seminars, meetings are provided online. People go out after taking necessary preparations like putting on masks and maintaining social distance to protect themselves and others. It has become a new normal thing and it will be passed onto the world after this pandemic thoroughly. We are getting used to a new normality. We are bound to step out only with proper equipment like masks. This is our call as a community, this is our ethical and moral compass which should be leading us in this period of reconstruction. It entangles every social realm, more and more countries are on restricted mode and some are on total shut down mode which boldly affect education, health care, economic sectors, business world, domestic spheres and what not! Anxiety, depression, crime, domestic violence, increasing divorce rate; these all came voluntarily with this pandemic as a package. To deal with a bizzare like that, it is taking all of us a lot to cope up with, to survive through this.